2014
DOI: 10.1080/00918369.2014.951261
|View full text |Cite
|
Sign up to set email alerts
|

Men Who Have Sex With Men in Kisumu, Kenya: Comfort in Accessing Health Services and Willingness to Participate in HIV Prevention Studies

Abstract: Men who have sex with men (MSM) are a crucial and marginalized at risk population for HIV in Africa but are poorly studied. Like other areas of Africa, homosexuality is illegal in Kenya. We assessed MSM comfort in accessing health services and willingness to participate in HIV prevention research in Kisumu, Kenya—an area of high HIV prevalence. We conducted a two-phase formative study with individual interviews (n = 15) and a structured survey (n = 51). Peer contact or snowball method (n = 43, 84.3%) was the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 15 publications
(26 reference statements)
1
36
0
Order By: Relevance
“…The gaining of knowledge through research participation was mentioned 16 times overall, ranked in the top three reasons four times, and was given as the top reason in one paper to participate . Knowledge was ranked fifth in Sub‐Saharan Africa and Eastern Europe, in HIV research, by male and patient participants and for hypothetical studies.…”
Section: Resultsmentioning
confidence: 99%
“…The gaining of knowledge through research participation was mentioned 16 times overall, ranked in the top three reasons four times, and was given as the top reason in one paper to participate . Knowledge was ranked fifth in Sub‐Saharan Africa and Eastern Europe, in HIV research, by male and patient participants and for hypothetical studies.…”
Section: Resultsmentioning
confidence: 99%
“…Homosexuality was decriminalized in South Africa over 20 years ago, but is still unlawful in Kenya [16, 17]. A survey among MSM in Kisumu, Kenya reported that 60% were uncomfortable seeking care in a public hospital [18]. That survey reported a high willingness of MSM to be contacted for participation in future HIV research studies.…”
Section: Discussionmentioning
confidence: 99%
“…That survey reported a high willingness of MSM to be contacted for participation in future HIV research studies. However, in-depth interviews revealed that the main reason for not wanting to participate was fear of personal information being shared outside of the study [18]. …”
Section: Discussionmentioning
confidence: 99%
“…As a result, they have poor access to care and may lack trust in providers [11,12]. In a small cohort on the Kenya coast, we found that MSM struggled with antiretroviral therapy (ART) adherence and had worse clinical outcomes compared with other high-risk individuals, including female sex workers and men with multiple sex partners [13].…”
Section: Introductionmentioning
confidence: 99%